2006
DOI: 10.1016/j.jneuroim.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium screening for multiple sclerosis implicates JAG1 and POU2AF1 as susceptibility genes in Europeans

Abstract: By combining all the data available from the Genetic Analysis of Multiple sclerosis in EuropeanS (GAMES) project, we have been able to identify 17 microsatellite markers showing consistent evidence for apparent association. As might be expected five of these markers map within the Major Histocompatibility Complex (MHC) and are in LD with HLA-DRB1. Individual genotyping of the 12 non-MHC markers confirmed association for three of them--D11S1986, D19S552 and D20S894. Association mapping across the candidate gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Jagged-1 has been found to be highly expressed in hypertrophic astrocytes within and around active MScl plaques lacking remyelination, while, in contrast, there was negligible jagged-1 expression in remyelinated lesions suggesting involvement of the Notch pathway in remyelination in MScl [21]. Later, linkage equilibrium screening implicated a number of genes, including the jagged-1 gene, as susceptibility genes for MScl in a large contingent of Europeans [22]. It has also been suggested that jagged-1 has therapeutic potential in the treatment of CD8 + T cell mediated diseases, due to it's ability to deliver indirect negative signals into CD8 + T cells in vivo [23].…”
Section: Discussionmentioning
confidence: 99%
“…Jagged-1 has been found to be highly expressed in hypertrophic astrocytes within and around active MScl plaques lacking remyelination, while, in contrast, there was negligible jagged-1 expression in remyelinated lesions suggesting involvement of the Notch pathway in remyelination in MScl [21]. Later, linkage equilibrium screening implicated a number of genes, including the jagged-1 gene, as susceptibility genes for MScl in a large contingent of Europeans [22]. It has also been suggested that jagged-1 has therapeutic potential in the treatment of CD8 + T cell mediated diseases, due to it's ability to deliver indirect negative signals into CD8 + T cells in vivo [23].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from preclinical models that Notch signals play important roles in the regulation of physiological processes underlying MS is incontrovertible. Furthermore, a large-scale linkage disequilibrium screen of 13,896 individuals identified JAG1 as a susceptibility gene for MS in Europeans (Games Collaborative Group et al, 2006), and a network analysis of the human T-cell activation network also indicated JAG1 as a potential therapeutic target (Palacios et al, 2007).…”
Section: Oligodendrocytes and Msmentioning
confidence: 99%
“…In contrast to Oct1, OCA-B whole-body knockouts are viable and fertile 26 . Polymorphisms in the Ocab (Pou2af1) locus are associated with autoimmune diseases, including MS 27,28 . Although its expression is 50-100 fold lower in T cells compared to B cells 29 , targeting either OCA-B by genetic deletion in T cells or its downstream pathways with a membrane-permeable peptide mimic suppresses type-1 diabetes 31 .…”
Section: Million Individuals Worldwide Suffer From Multiple Sclerosis...mentioning
confidence: 99%